2016
DOI: 10.3892/ol.2016.4686
|View full text |Cite
|
Sign up to set email alerts
|

Huaier polysaccharide induces apoptosis in hepatocellular carcinoma cells through p38 MAPK

Abstract: Abstract. The underlying mechanism of the antitumor activity of Huaier polysaccharide (HP) remains to be explored. The present study aimed to investigate the inhibitory effect of HP on hepatocellular carcinoma (HCC) cells, and to explore the possible mechanisms of its anticancer effect. Cell viability was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, while apoptotic nuclear changes were observed using Hoechst 33258 staining. The distribution of cell cycle and apoptosis were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
1
30
1
Order By: Relevance
“…However, our results are in contrast with previous studies showing that activation of the ASK1‐p38 MAPK signalling cascade induces apoptosis in many HCC cell lines . Additionally, Bao et al reported that p38 MAPK induces apoptosis in HepG2 and Huh7 cells through upregulation of apoptosis‐related proteins, including p53, caspases and Bcl‐2 proteins …”
Section: Discussioncontrasting
confidence: 99%
“…However, our results are in contrast with previous studies showing that activation of the ASK1‐p38 MAPK signalling cascade induces apoptosis in many HCC cell lines . Additionally, Bao et al reported that p38 MAPK induces apoptosis in HepG2 and Huh7 cells through upregulation of apoptosis‐related proteins, including p53, caspases and Bcl‐2 proteins …”
Section: Discussioncontrasting
confidence: 99%
“…Huaier extract has been found to not only have an antitumor effect, but also enhance the sensitivity of cancer cells to chemotherapy drugs and improve immunity and long-term prognosis in cancer patients (29,30). Bao et al (18) found that the Huaier extract inhibited the proliferation of human hepatocellular carcinoma Hep-G2 cells and induced cell apoptosis in a concentration-dependent manner. In the present study, after treating MCF-7 and MDA-MB-231 cells with Huaier extract for 24 and 48 h, we found that Huaier extract inhibited cell proliferation, reduced cell viability and promoted cell apoptosis in a time-and dose-dependent manner, results which were consistent with a study from Zhang et al (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the main anticancer mechanisms of Huaier are achieved by inhibiting the growth and proliferation of cancer cells, inducing apoptosis, decreasing drug resistance in cancer cells, and improving immunity as well (16,17). In vitro experiments revealed that Huaier extract inhibited the growth of hepatocarcinoma and human lung adenocarcinoma cells (18,19). Huaier extract could inhibit the growth of ERα-positive breast cancer cells through the ERα/NF-ÎșB pathway (20).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and causes approximately 600,000 deaths every year (1,2). Although liver transplantation and surgical resection are the most efficient therapeutic strategies for early stage HCC (3,4), the majority of patients, who are usually diagnosed at an advanced stage, must rely on traditional chemotherapies (5).…”
Section: Introductionmentioning
confidence: 99%
“…Thioredoxin interaction protein (TXNIP) is a 46 kDa protein that was first identified in an HL-60 leukemia cell line treated with 1α, 25-dihydroxyvitamin D 3 [1,25(OH 2 ) D 3 ] (11). As a negative regulator of thioredoxin (TRX), TXNIP was found to be an inducer of the intracellular level of reactive oxygen species (ROS) (12).…”
Section: Introductionmentioning
confidence: 99%